(untitled) - Fourie, Franco

The development of a smart monitoring system for solar pv plants by employing AES-encrypted LoRa wireless sensor networks. (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.